Double-Osmotic-Shock Procedure to Prepare Gentamicin Adenine Mononucleotide Transferase for the Enzymatic Assay of Gentamicin - Dankert, J. (1977)
The release of gentamicin adenine mononucleotide transferase during single, cold, osmotic-shock treatment of Escherichia coli K-12 W677/HJR66 is not always maximal. The quantity of gentamicin adenine mononucleotide transferase in osmotic extracts could be significantly increased when a double-shock procedure was performed.